Injectable Multi-Drug Loaded Hydrogels for Contraception - Nie, Lei; Zou, Peng; Sun, Meng; Han, Yanting; Ji, Chingching; Zhou, Qiuju; Suo, Jinping (New Ideas Concerning Science and Technology Vol. 5, 2021)
Injectable intravaginal hydrogels could deliver drugs systemically without a hepatic first-pass effect. The vaginal route has many advantages due to its large surface area, rich blood supply, relatively high permeability of many drugs, and self-insertion. This paper focuses on the contraceptive function of an injectable temperature-sensitive four-arm star-shaped poly(D,L-lactic-co-glycolic acid)-b-methoxy poly(ethylene glycol) (4sPLGA-mPEG) block copolymer hydrogels as a carrier of three drugs. In vitro controlled release profiles were investigated via HPLC, and it showed that the cumulative release amounts of indomethacin (IMC), gestodene (GSD), and ethinyl estradiol (EE) from copolymer hydrogels could be regulated by adjusting the lactide/glycolide (LA/GA) mol ratio. In addition, in vitro release profiles of IMC, GSD, and EE well corresponded to Higuchi model. The acute toxicity of copolymer hydrogels loaded with different dosage contents multi-drug was evaluated in vivo. As to the high dosage group, the uterus was hydropic at day 1 and ulcerated at day 5, followed by intestinal adhesion. Regarding the middle dosage group, no festering of tissues was observed and, blood coagulum existed in the uterus on different days. For low dosage group, no significant tissue necrosis was found. Finally, the antifertility experiments confirmed that hydrogels loaded with the multi-drug had an excellent contraceptive effect. The above results indicated that injectable copolymer hydrogel as a multi-drug carrier was promising as a novel contraception method.